Making Sense of Mud: The Use of Benthic Foraminifera in Mudstone Sedimentology, Sabah, North Borneo - Jon Noad; Rachel Preece (Berita Sedimentologi, 2014)
The use of microfossils in the dating of sedimentary rocks is commonplace, and well documented. However, the use of these fossils, particularly benthic foraminifera, in the interpretation of depositional environments has received less attention. A series of mudstone samples collected from five formations outcropping in eastern Sabah, NE Borneo, ranging in age from Eocene to Pliocene in age, has yielded more than 80 species of calcareous and agglutinated foraminifera. These have been interpreted to give both stratigraphical and depositional information.The microfossil assemblages are interpreted to represent conditions ranging from those inhabiting mangroves, very shallow marine to paralic coastal settings, through to open marine, relatively anoxic settings. These interpretations are supported by the interpreted sedimentology of measured outcrop sections. The preservation, size of individual tests, species diversity and diagenetic signatures have been combined to provide a detailed picture of conditions extant at the seabed during deposition of these sediments. This includes oxygen and energy levels, as well as evidence of post mortem dissolution. Around 60% of the samples yielded a very limited fauna, or were barren. Among the assemblages identified are deep marine 'flysch-type faunas' that are also comparable to the Agua Salada Fauna of Northern Venezuela.The synthesis of foraminiferal and sedimentological data provides a powerful tool in identifying depositional environments in seemingly homogenous mudstone beds. Hence it can be used as a correlation tool. Through applying the process described here to hydrocarbon exploration, it is possible to extrapolate additional information on depositional settings from core, and hence provide sequence stratigraphic architectural trends. These can be used to predict source rock distribution. This approach may also be applied to cuttings data in the absence of well logs or core.